Effect of educational content creators on student motivation and learning outcomes in the pandemic COVID-19 - Afni Zahrotulmuna Sya’ro; Eka Puspa Dewi (Curricula: Journal of Curriculum Development, 2022)
The limitations that exist during the COVID-19 pandemic, it requires all people to connect to the internet. As well as in distance learning, students have to look for learning material from other sources. This research is motivated by the fact that students often watch learning videos from educational content creators to look for subject matter that is not yet understood. The purpose of this study is to determine the effect of educational content creators on learning methods, motivation and student learning outcomes. The method used in this research is qualitative and quantitative methods and data collection techniques by distributing questionnaires to target participants, namely junior high school students, high school students and university students. From the research results, it can be seen that the development of instructional video media carried out by educational content creators can increase student motivation and learning outcomes during the COVID-19 pandemic.   Abstrak Keterbatasan yang ada di masa pandemi COVID-19 mengharuskan semua kalangan masyarakat berhubungan dengan internet. Serta dalam pembelajaran jarak jauh membuat siswa harus mencari materi pembelajaran dari sumber lain. Penelitian ini dilatarbelakangi oleh adanya fakta bahwa siswa sering menonton video pembelajaran dari content creator edukasi untuk mencari materi pelajaran yang belum dipahami. Tujuan dari penelitian ini yaitu untuk mengetahui pengaruh content creator edukasi terhadap cara belajar, motivasi dan hasil belajar siswa. Metode yang digunakan pada penelitian ini ialah dengan metode kualitatif dan kuantitatif dan teknik pengumpulan data dengan menyebarkan kuesioner kepada target partisipan yaitu siswa SMP, SMP dan Mahasiswa. Dari hasil penelitian dapat diketahui bahwa pengembangan media video pembelajaran yang dilakukan oleh content creator edukasi dapat meningkatkan motivasi dan hasil belajar siswa di masa pandemi COVID-19. Kata Kunci: COVID-19; hasil belajar siswa; konten kreator edukasi; motivasi belajar; sumber belajar